The Effects of Planting Systems and Nitrogen and Phosphorus Combined Fertilizer on Yield and Yield Components of Maize (Zea mays L.) in Eastern Ethiopia. - Hassen Abdulahi; Ed Sarobol; Vichan Vichukit; Chairerk Suwannarat (Agriculture and Natural Resources, 2005)
A field experiment was conducted during the rainy seasons of 2003 and 2004 in Eastern Ethiopia to assess the effects of planting systems and nitrogen and phosphorus combined fertilizer on yield and yield components of maize (Zea mays L.) and also to investigate the interaction effect of tie-ridge and NP combined fertilizer on yield. Yield and other related parameters studied were affected by planting systems and showed an increment in tie-ridge planting system as compared with flat bed, and it was concluded that the tie-ridge might have conserved larger amount of soil moisture ans this resulted in higher seed yield. NP combined fertilizer had a significant effect on yield and other parameters, among the combined NP fertilizers in this study, 41-46 kg N-P2O5/ha gave the highest yield, though it was statistically at par with 64-46 kg N-P2O5/ha. Variety had also a significant effect on yield and other parameters, and Melkassa I variety performed better than the local variety. Interaction between planting systems and NP combined fertilizer was significant for yield, indicating that there is a need to determine planting system for NP combined. N1P1 and N2P1 gave better result in tie-ridge planting system.